Kinetic studies on recombinant stem bromelain - Bala, Muntari; Mel, Maizirwan; Jami, Mohammed Saedi; Amid, Azura; Salleh, Hamzah Mohd. (SciRes., 2013)
Stem bromelain is a plant thiol protease with several industrial and therapeutic applications. This current work presents kinetic studies of recombinant bromelain (recBM) expressed in Escherichia coli BL21-AI on foursynthetic substrates, N-α-carbobenzoxy-L-alanyl-p-nitrophenylester (ZANPE), N-α-carbobenzoxy-L-arginyl-L-ar-ginine-p-nitroanilide (ZAANA), N-α-carbobenzo-xy-L-phenylalanyl-L-valyl-L-arginine-p-nitroanili-de (ZPVANA) and L-pyroglutamyl-L-phenylalanyl-L-leucine-p-nitroanilide (PFLNA). Hydrolytic activities of recBM at various pH and temperature conditions were compared to that of commercial bromelain (cBM). Both enzymes demonstrated high activities at 45o C and pH 5 - 8 for recBM and pH 6 - 8 for cBM. recBM showed marginally lower Kmand slightly higher kcat/Kmfor ZAANA, ZANPE and ZPVANA in comparison to cBM.trans Epoxysuccinyl-L-leucylamido {4- guanidino}butane (E-64) severely affected recBM and cBM hydrolysis of the synthetic substrates by competitive inhibition with Kivalues of 3.6 - 5.1 μM and 5.5 - 6.9 μM for recBM and cBM, respectively. The evaluated properties of recBM including temperature and pH optima, substrate specificity and sensitivity to inhibitors or activators, satisfy the requisites required for food industries.